PREPARATION AND EVALUATION OF PERIODONTAL STRIPS OF GATIFLOXACIN FOR PERIODONTAL DISEASES. - MOHAMMED GULZAR AHMED,; NARAYANA CHARYULU.R,; KANTHRAJ.K,; HARISH.N.M,; PRABHAKAR PRABHU, (International Journal of Pharma and Bio Sciences, 2010)
Gatifloxacin is a broad-spectrum antimicrobial agent, which is active against a number of aerobic, anaerobic, gram positive and gram negative periodontal pathogens. In the present investigation, chitosan strips containing Gatifloxacin (10%, 20% and 30% to the weight of polymer) were prepared by solution casting method using 1% v/v acetic acid in water. Further strips containing 30% gatifloxacin were cross-linked by exposing to the vapours of 2% v/v glutaraldehyde in water intended to extended the release. Macroscopical features revealed that drug was dissolved in the polymer matrix rather than dispersing. The prepared films were evaluated for their thickness, content uniformity, weight variation, tensile strength, hardness and in-vitro dissolution. The average weight and thickness of both the crosslinked and uncross-linked strips were uniform. There was a reduction in the tensile strength and increase in hardness when the films were cross-linked. Static dissolution studies showed a burst release initially followed by a progressive fall in the release of the drug and extended upto 19 days once the strips were cross-linked. Release kinetics of gatifloxacin from chitosan strips followed the higuchi’s diffusional model and also showed zero order release profile.